GOOD CORPORATE CULTURE - Moeljono, Djokosantoso (Benefit, 2005)
This article discusses corporate culture in business. In this paper, good corporate culture is themain corporate culture, which influences company performance. There are several principal componentsin good corporate culture; they are transparency, accountability, and appropriateness. This article alsodiscusses corporate culture of BRI. There are integrity, professionalism, customer satisfaction, andhuman resource development